Total Coliforms and Turbidity Removal of Water in the Continuous Sand Filter - AH Mahvi; R Sheikhi; K Naddafi (Iranian Journal of Public Health, 2003)
The continuous filter is a kind of sand filter, which will operate without any interruptions for backwashing and also it accepts high-suspended solid levels in feed stream. Fouled sand is continuously removed from the filter bed, washed and recycled back without interruption with filtration process. Various samples of water with certain amounts of turbidity enter through a feed pipe and being distributed to the filter. A central column runs from top to bottom of the filter. The water is led through an outer tube in the column by a set of radial, distributor arms. The polluted water flows up ward through the sand bed. The water emerges; clean, in the top section of the tank, and eventually spills over a weir, and then inters into a discharge pipe. In this research, the continuous sand filter was studied to determine its disinfection efficiency in addition to turbidity removal. The results showed that the filtered water had a high quality and the turbidity reduction was 95.5 %. Inspecting the work of the filter had revealed that the removal rates of coliforms and microbial colonies were 99.67 % and 98.99 % respectively. On the other hand, by the use of direct filtration, turbidity reduction was over 97 %. In direct filtration, drinking water with less than 1 NTU turbidity was provided. This continuous sand filter has the advantage of stable operation and more energy saving as compared to the conventional ones.